Tuberculous pericarditis with tamponade diagnosed concomitantly with COVID-19: a case report. Issue 1 (28th December 2020) - Wong, Shiun Woei; Ng, Jessica Ke Xuan; Chia, Yew Woon
Abstract: Background: Tuberculous pericarditis is a rare manifestation of tuberculosis infection. COVID-19 pandemic poses a challenge in detecting uncommon diseases. Case summary: A 47-year-old man was admitted with symptoms of COVID-19 infection. Rapid progression of cardiomegaly on radiograph with clinical deterioration were suggestive of pericardial tamponade. Urgent pericardiocentesis revealed haemoserous fluid, elevated adenosine deaminase, and positive tuberculous (TB) polymerase chain reaction (PCR). He was started on anti-TB therapy and Remdesivir with marked improvement of symptoms. Repeat echocardiogram and CT thorax showed resolution of pericardial fluid, and the patient remained well on discharge. Discussion: This case highlights the difficulty in detecting a concomitant rare but important disease. The development of massive pericardial tamponade acutely is not pathognomonic for COVID-19, and a careful diagnostic process involving multi-modality imaging occurred to arrive at a diagnosis of tuberculosis.